Low reynolds propellers for increased quadcopters endurance - Carvalho, Isa Diana de Sousa Baptista Morais (2014)
Submitted by Joana Lopes Dias (jdias@ubi.pt) on 2014-07-02T14:07:11Z No. of bitstreams: 1 DISSERTAÇÃO Diana.pdf: 1565027 bytes, checksum: 362402a061a5dda7c6c795004159c0d9 (MD5)